Cultural Practices and Academic Performance of Blaan Pupils in Sinapulan Elementary School - Mark Steve Alentajan Francisco; Dolorcita Ebona Pauya; Cristobal Millenes Ambayon (BIRCU, 2021)
This study generally aimed to determine the level of cultural practices and academic performance of the Blaan pupils in Sinapulan Elementary School, Sinapulan, Columbio, Sultan Kudarat. Moreover, it was intended to find out which of these practices are still prevalent. The study employed the descriptive method of research. The researchers utilized a self-formulated survey questionnaire which was validated and approved by a panel of experts. The same underwent tests of validity and reliability. The statistical tools utilized in the study were mean, standard deviation, t-test, ANOVA and correlation. Majority of the respondents were males, whose parents were elementary graduates. The extent of cultural practices as perceived by Blaan pupils was Highly Evident. Their level of academic performance was Satisfactory. There was a significant relationship between the pupils’ extent of cultural practices and their academic performance. There were no significant differences in their academic performances as to gender, age, parents’ educational attainment and monthly family income.